Tinjauan kembali temuan butir pati Triticeae pada kalkulus gigi rangka manusia Situs Plawangan, Rembang: Tinjauan Kembali Temuan Butir Pati Triticeae pada Kalkulus Gigi Rangka Manusia Situs Plawangan, Rembang - Arrozain, M. Dziyaul F.; Puspitasari, Intan; Noerwidi, Sofwan (BRIN, 2025)
The extraction of plant micro remains from the dental calculus of human remains at the Plawangan site yielded a starch grain. Preliminary analysis with a limited reference sample suggested that the starch indicated the consumption of cereal from the Triticeae plants, specifically wheat or barley, in the early AD. This article aims to reassess the starch previously identified as belonging to the Triticeae. The starch was re-examined using descriptive-qualitative and multivariate comparative analyses, including LDA and cluster analysis. The data used were wheat and barley starch reference samples extracted from fresh plants. The result demonstrated that the starch from the dental calculus was not origin from Triticeae, particularly wheat and barley. This was due to the primer difference in surface area. The result also invalidated the initial interpretation suggesting the consumption of wheat or barley at the Plawangan site in the early AD.